The Simulated Acculturation Model in the FOUNTAINS-Game. (February 2015) - Männamaa, Ivar; Leijen, Äli
Background. The problems and benefits of amulticultural society are actively discussed in many countries. FOUNTAINS is a table-top simulation game designed as a study aid to enhance comprehension ofcultural integration processes. The game was developed for use in regular classroom settings and has been successfully tested with several groups of participants. The design of the game is based on thebi-dimensional model of acculturation that focuses on the joint issues of maintaining one's culture and involvement indecision making . It also introduces the dilemma ofcooperation andcompetition in a situation oflimited resources . Participants must find ways topreserve their own comprehensive culture and at the same time provide other groupsaccess to resources . Aim. The article examines thedynamics of the game and describes its basicdesign . Therules of the game and suggestions fordebriefing are provided in an accompanying article – this issue. The purpose of the study was toevaluate the game'svalidity and to assess the potential educationalvalue andusability of the game. Method. FOUNTAINS was piloted with several groups, and a brief post-gamequestionnaire was conducted toevaluate learning outcomes. Experts of both integration and gaming were asked to evaluate the game; theirfeedback on theusability of the game referred to the face value of the game as an educational tool. After piloting the game was introduced to teachers, the majority of whom expressed willingness to use the game in their classes. Conclusion. The article concludes with the basicresults of the evaluation. In spite of some limitations it can be said that FOUNTAINS is anefficient learning aid that works well with different age groups.